Gold prices: Analyzing its cyclical behavior - Martha Gutiérrez; Giovanni Franco; Carlos Campuzano (Lecturas de Economía, 2013)
Gold prices: Analyzing its cyclical behavior Abstract: Gold is a commodity that is seen as a safe haven when a financial crisis strikes, but when stock markets are prosperous, these are more attractive investment alternatives, and so the gold cycle goes on and on. The DJIA/GF (Dow Jones Industrial Average and Gold Fix ratio) is chosen to establish the evolution of gold prices in relation to the NYSE. This paper has two goals: to prove that the DJIA/GF ratio is strongly cyclical by using Fourier analysis and to set a predictive neural networks model to forecast the behavior of this ratio during 2011-2020. To this end, business cycle events like the Great Depression along with the 1970s crisis, and the 1950s boom along with the world economic recovery of the 1990s are contrasted in light of the mentioned ratio. Gold prices are found to evolve cyclically with a dominant period of 37 years and are mainly affected by energy prices, financial markets and macroeconomic indicators.